RANCANG BANGUN ALAT BANTU PERAKITAN DAN PENGELASAN KURSI LABORATORIUM (LAB STOOL) - Sunding, Alang; Ridhani, Ulia; Burhan, Imron (Jurnal Teknologi Terapan, 2018)
The quality of mass produced lab stools are determined based on the similarity of shape andsize of the labs stools produced. Assembly work is done by two technicians for 55 minuteswithout using assembly tools (Fixture). Based on this data, it can be inferred that in termsof working time assembly  process is considered too long or inefficient in terms of time.Based on the amount of labor it is still not efficient or the productivity is still low, so theremust be innovations made to speed up the assembly time. in addition to low productivity,without assembly tools and welding the product is not similiar because there is a change ofshape  after  welding  process.  It  means  the  quality  of  the  product  is  not  good. Businesscompetition in the field of metal furniture manufacture is growing so that producers have tothink of methods to improve productivity, quality and speed up production time. To increaseproductivity,  it  is  necessary  to  assemble  and  fix  the  parts  to  be  assembled to  eliminateunwanted  movement  due  to  the  welding  distortion. The  use  of  fixtures  in  the  assemblyprocess can be done by one person with an average processing time of 25 minutes.